Evolution of Norms for a Trustworthy AI Society and Our Responsibilities and Roles - JiHun Lim; Jeongeun Seo; HunYeong Kwon (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Artificial Intelligence (AI) holds promising opportunities for enhancing human life, yet its pervasive influence on society also introduces unintended negative consequences. Throughout the 2010s, a growing recognition of ethical concerns in AI led to the formulation of principles emphasizing ethical research and development. Various global entities have since endeavored to establish norms for AI ethics. Recently, beyond the declaration of ethical principles, concrete practical guides and codes of conduct are emerging, and in some countries, they are developing into specific legal regulatory discussions. This paper provides a detailed examination of the evolutionary trajectory of AI norms and further explores the responsibilities and roles of diverse stakeholder groups, including developers, suppliers, and users, in ensuring the trustworthiness of AI. The analysis aims to move beyond abstract ethical principles to actionable norms, emphasizing the need for a holistic societal response.